Corrosion Behavior and Mechanical Properties of Ultrafine‐Grained Pure Copper with Potential as a Biomaterial1. Issue 4 (6th October 2015) - Gholami, Mozghan; Mhaede, Mansour; Pastorek, Filip; Altenberger, Igor; Hadzima, Branislav; Wollmann, Manfred; Wagner, Lothar
Abstract : This study aims to evaluate and compare the mechanical and corrosion resistance properties of ultrafine‐grained (UFG) copper with that of coarse‐grained (CG) copper microstructures. Ultrafine‐grained microstructures are produced through severe plastic deformation using rotary swaging. Potentiodynamic polarization and electrochemical impedance tests are performed at 37 °C in Hank's solution as the simulated body fluid. The results reveal that the highly deformed UFG‐materials not only show marked enhancement of the mechanical properties but also remarkable enhancement of corrosion resistance compared with that of the CG counterpart. Abstract : Ultra grain refinement of Cu leads to a marked increase of the tensile strength. The Corrosion resistance increased by slight swaging then decreased with further swaging, as indicated in the TOC Figure. Release of Cu 2+ increased by slight swaging then decreased with further deformation.